The characteristics of proactive personality and auto-aggressive behaviour of convicted men serving a prison sentence - Kwiatkowski, Bartosz (Studia Psychologica: Theoria et praxis, 2020)
The obligation to be imprisoned in penitentiary isolation causes personal damages in the form of emotional, motivation or behavioral disorders. The negative effect of depriving needs of prisoners is their increased tendency to perform intentional self-harm while serving imprisonment. Besides to the factors contributing to the occurrence of self-aggressive behaviors, there are also protective factors that are undoubtedly less often subject to psychological studies. The study involved 50 convicted men serving their sentences once again in their lives. To determine the level of their proactivity, The Scale of Proactivity in Penitentiary Isolation (PPI) was used, while their propensity to self-aggression was determined using The Inventory of Statements about self-injury (ISAS). The article discusses the results of our own research, which proved that proactivity as a personality trait has a negative relationship with self-aggression. Proactive actions aimed at gaining a sense of self-competence and family support are most important in the protection against the self-aggresion behaviour of convicts. Moreover, the study showed that proactive convicts have significantly longer intervals between acts of self-aggression, as well as their proactive activities coexist with declarations of the desire to stop self-harm in the future.